Endoscopic and Radiographic Findings and OperativeTreatment of a Dog with Mechanical Ileus - Baydar, Ersoy; Durmuş, Ali Said; Polat, Eren; Tümer, Kenan Çağrı (My University, 2021)
In the present case report, a 3-year-old male Golden Retriever dog was referred to Fırat UniversityAnimal Hospital with complaints of weakness, vomiting and inability for defecation. After theclinical, radiographic and endoscopic examinations, it was found that the dog had mechanical ileusdue to swallowing a thick bandage about 2 meters long and 10 cm wide. The aim of this report is tocontribute to the literature by sharing the diagnosis and operative treatment method applied in thiscase.
Keywords: Veterinerlik; Cerrahi